Watermarking medical signals for telemedicine. - Xuan Kong
The modern telecommunication infrastructure supports the possibility of delivering quality health care without the physical presence of medical experts. The integrity of biomedical signals being transmitted through the communication channels must be established before their utilization. This paper investigates three digital watermarking techniques for signal integrity verification in an electroencephalogram (EEG) monitoring application for brain injury detection. The techniques studied are the patchwork, least-significant bit and quantization watermarking methods. The three techniques are evaluated and compared in the following areas: sensitivity to noise contamination, robustness to EEG signal characteristic changes due to brain injury, and consistency under various communication channel models. The patchwork method performs best for noise contamination rejection among the three methods. The noise contamination detection rates of all three methods remain relatively stable across a wide range of EEG characteristics.
Keywords: EEG compression; EEG monitoring application; EEG signal characteristic change robustness; Biomedical signal integrity verification; Brain injury detection; Communication channel models; Consistency; Digital watermarking techniques; Electroencephalogram; Least-significant bit method; Noise contamination detection rate; Noise contamination rejection; Noise contamination sensitivity; Patchwork method; Quality health care delivery; Quantization method; Telecommunication infrastructure; Telemedicine